MEASURING THE EFFECT OF SALARY RAISE OVER THE PERFORMANCE OF SALES PROFESSIONALS – THE CASE OF AN INTERNATIONAL ORGANIZATION - Dimovska, Nena; Eftimov, Lјupcho (Ss Cyril and Methodius University, Faculty of Economics-Skopje, 2020)
Should fixed salary be the single and most appropriate tool for motivating employees; or should management consider a more diverse, innovative tools for motivation, based on multiple factors? Does a salary increase always guarantee ROI? Also, will sales professionals be motivated by an incremental, equal-to-all salary increase? This paper elaborates these and similar dilemmas and presents a research conducted in the sales sector, in a medium-sized international firm. It represents consequences of applying an equal and applicable to all salary increase of 10%. Тhe paper tries to reject traditional beliefs (and awards distribution models) that salary, per se, is the highest source or motivation and a guarantee for improving performance. Тhe research shows how sales professionals are affected by incremental salary increase, and tries to provide recommendations for further research on effective, cost-efficient award strategies that increase motivation and performance and can be easily adopted in similar organizations.